1. If f(x) = x^2 + x and g(x) = 2x - 1, find [f * g](x)

2.f(x) = x^2 + x and g(x) = 2x - 1, find [g * f](x)

Thank you so much!

Probably you mean composition of functions. Then

f(g(x)) = f(2x - 1) = (2x - 1)^2 + (2x - 1) = (2x - 1)*2x = 4x^2 - 2x.

g(f(x)) = g(x^2 + x) = 2(x^2 + x) - 1 = 2x^2 + 2x - 1.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up